Peningkatan Self Leadership dalam Merencanakan Karir melalui Layanan Informasi Daring Model Cooperative Learning - Malthelda Yulianti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
This counseling guidance class action study aims to improve self leadership in planning career through online information servis of cooperative learning model. The subjects of the study were the students of class XII MIPA-1 SMA Negeri 2 Yogyakarta. The research method is observation using instruments compiled by researchers with reference to the theoretical studies used. Data analysis techniques use qualitative descriptive techniques, namely describing the implementation of online information services of cooprlearning model from the planning th stage, implementation of actions, observations and reflections on each cycle. The data collected from the research instruments in the first cycle were then compared with the data in the second cycle. The results study showed that there is an increase in the self leadership ability of learners, in the aspect category of the self awareness from 75.88% to 84.38% increased by 7.50%. In terms of from 78.12% to 88.27% increased by 10.60%. Furthermore the self management aspect from 76.56% to 85.93% increased by 9.37%. While in the aspect of self accomplishment from 78.11% to 82.83% increased by 4.72%. From the results of this counseling guidance class action research can be concluded that online information service of cooperative learning model can increase the self leadership in planning careers of students of class XII MIPA-1 SMA Negeri 2 Yogyakarta.